Principles of modern manufacturing - Groover, Mikell P., 1939- (Hoboken, N.J. : Wiley, 2011)
Engineers rely on Groover because of the book s quantitative and engineering-oriented approach that provides more equations and numerical problem exercises. The fourth edition introduces more modern topics, including new materials, processes and systems. End of chapter problems are also thoroughly revised to make the material more relevant. Several figures have been enhanced to significantly improve the quality of artwork. All of these changes will help engineers better understand the topic and how to apply it in the field.
1.Introduction and Overview of Manufacturing 2.The Nature of Materials 3.Mechanical Properties of Materials 4.Physical Properties of Materials 5.Dimensions, Surfaces, and Their Measurement 6.Metals 7.Ceramics 8.Polymers and Composite Materials 9.Fundamentals of Casting 10.Metal Casting Processes 11.Glassworking 12.Shaping Processes for Polymers 13.Shaping Processes for Rubbers and Polymer Matrix Composites 14.Powder Metallurgy 15.Processing of Ceramics and Cermets 16.Fundamentals of Metal Forming 17.Bulk Deformation Processes in Metal Working 18.Sheet Metalworking 19.Theory of Metal Cutting 20.Machining Operations and Machine Tools 21.Cutting Tool Technology 22.Economic and Product Design Considerations in Machining 23.Grinding and Other Abrasive Processes 24.Nontraditional Machining and Thermal Cutting Processes 25.Heat Treatment of Metals 26.Surface Processing Operations 27.Fundamentals of Welding 28.Welding Processes 29.Brazing, Soldering, and Adhesive Bonding 30.Mechanical Assembly 31.Rapid Prototyping 32.Processing of Integrated Circuits 33.Electronics Assembly and Packaging 34.Microfabrication and Nanofabrication Processes 35.Automation Technologies for Manufacturing Systems 36.Integrated Manufacturing Systems 37.Manufacturing Engineering 38.Production Planning and Control 39.Quality Control and Inspection.
Includes bibliographical references and index.
DVD: Fundamental manufacturing processes sampler
Keywords: Production engineering; Manufacturing processes